Enhancing Mechanisms for Protecting Women's Rights within Islamic Family Law: A Comparative Study of Indonesia and Middle Eastern Practices - Arifin Nugroho; Ratna Dewi (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2020)
This research examines the comparison of mechanisms for protecting women's rights in Islamic family law between Indonesia and several Middle Eastern countries. Using a comparative qualitative approach, this study collects data through in-depth interviews, document studies, and content analysis from relevant legal sources. The research results show that there are significant differences in the interpretation and implementation of Islamic family law which have an impact on protecting women from domestic violence. In Indonesia, there is a tendency for more flexible and progressive interpretations towards the integration of the principle of gender equality in family law, whereas in Middle Eastern countries, more conservative interpretations often hinder the protection of women's rights. The study also explores the impact of women's rights advocacy and activism, which has played an important role in supporting legislative change and increasing public awareness. The resulting recommendations focus on developing strategies to increase the implementation of policies that are more effective in protecting women's rights, strengthening a supportive legal framework, and integrating the principles of justice and protection in Islamic family law.